The Impact of Digital RMB Promotion on China's Corporate Financial System and Policy Recommendations - Huang, Yifan (International Journal of Global Economics and Management, 2024)
With the deep development of the digital economy era, digital RMB, as an important form of central bank digital currency, plays an increasingly crucial role in China's financial system. It not only has all the functions of traditional currencies, but also shows unique advantages in enhancing payment efficiency, reducing transaction costs, and improving financial regulatory capabilities. This study conducted an in-depth analysis of the impact of the promotion of the digital RMB on China's corporate financial system by visiting and researching a number of enterprises and collecting financial data over a five-year period. The study finds that the promotion of digital RMB has facilitated the convenience of inter-company payments and settlements, enhanced the traceability of financial data, and positively impacted the enhancement of corporate credit availability and financial service innovation. However, there are also challenges such as increased costs for enterprises to adapt to the new system and risks of digital currency custody. Based on this, this paper constructs a multi-level analytical framework to systematically sort out the mechanisms of the impact of digital RMB on the corporate financial system, and puts forward a series of policy recommendations accordingly. These recommendations involve strengthening the construction of corporate digital infrastructure, coordinating the interface between digital RMB and existing financial regulatory policies, and enhancing corporate digital currency knowledge training. This study aims to provide theoretical support and empirical references for policy formulation and financial decision-making by government departments, financial regulators, and enterprises in the digital currency era.